Self-employment in the United Kingdom: the role of frictions and labor market institutions - Franca, Ítalo de Paula (2018)
We develop a job search model with self-employment and savings to understand occupation choice in the United Kingdom (UK). In the UK, self-employment has steadily grown from the beginning of the 2000s and comprised more than 14% of the workforce in 2015. We estimated the model using the method of moments and data from two longitudinal surveys, the Wealth and Assets Survey and the Understanding Society for the period 2010-12. We then use the model to simulate counterfactual policies to promote employment via entrepreneurship such as lower profit taxation and entry barriers into self-employment, or through changes in wage taxes and unemployment benefits. The results show that a rise in self-employment can be mostly associated with an increase in the payroll tax or a reduction on the self-employment income tax